Integrated information systems for management of agricultural enterprises of Ukraine - Moroz, Svitlana; Мороз, Світлана Іванівна (Іnternational Science Group, 2021)
Conditions of global competition, growing societal requirements for product quality and environmental friendliness, encourage Ukrainians agricultural enterprises to seek various means to improve the efficiency of production and marketing activities. One of the obvious ways is adaptive management and rapid response to changes in production and market factors based on reliable and timely information. Currently, this is possible due to the use of modern management methods, computer information systems, special business and mobile applications. The success of the implementation and use of integrated information systems largely depends on the interest of management and the willingness of professionals to work with information and use and develop software products, namely the availability of information culture. Обґрунтовано необхідність інтеграції інформаційних систем і технологій для управління вітчизняними аграрними підприємствами.
Інтеграція інформаційних систем для менеджменту сільськогосподарських підприємств України
Keywords: integration; інтеграція; integrated information systems; інтегровані інформаційні системи; management; менеджмент; agricultural enterprises; сільськогосподарські підприємства